HUBUNGAN KINERJA PERAWAT DENGAN IMPLEMENTASI PENCEGAHAN DAN PENGENDALIAN INFEKSI DI RUANG RAWAT INAP RS ANNISA - Zhafirah Zhafarina (2023)
Hospitals are places for people to get health care and services, and expect the best treatment. However, due to the high rate of Healthcare Associated Infections (HAIs) in hospitals, health workers must be able to carry out Infection Prevention and Control (PPI) measures; however, workload, work environment, motivation, and attitudes drive nurse performance in providing nursing care, which can have an impact on the implementation of PPI. The purpose of this study was to determine the relationship between nurse performance and respondent characteristics with the implementation of infection prevention and control in the hospitalization room of Annisa Hospital. The method in this study is descriptive analytic with a cross sectional approach with total sampling of 45 respondents. The results of the chi square test obtained a p-value <0.05 (0.001) which means that there is a significant relationship between nurse performance and the implementation of infection prevention and control. It can be concluded that the better the performance of nurses, the greater the chance of being able to carry out infection prevention and control measures properly. Researchers recommend improving the quality of nurses by providing retraining to nurses to increase experience and insight so that it will increase work ethic which is beneficial for the implementation of infection prevention and control implementation properly organized by hospital management